Time-delayed impulsive control for discrete-time nonlinear systems with actuator saturation - Li, Liangliang; Li, Chuandong; Zhang, Wei (Nonlinear Analysis: Modelling and Control, 2019)
This paper focuses on the problem of time-delayed impulsive control with actuator saturation for discrete-time dynamical systems. By establishing a delayed impulsive difference inequality, combining with convex analysis and inequality techniques, some sufficient conditions are obtained to ensure exponential stability for discrete-time dynamical systems via time-delayed impulsive controller with actuator saturation. The designed controller admits the existence of some transmission delays in impulsive feedback law, and the control input variables are required to stay within an availability zone. Several numerical simulations are also given to demonstrate the effectiveness of the proposed results.
Keywords: discrete-time dynamical systems; delayed impulsive control; exponential stability; actuator saturation